Blood-Brain Barrier Protein Claudin-5 Expressed in Paired Xenopus laevis Oocytes Mediates Cell-Cell Interaction - Brunner, Nora; Stein, Laura; Cornelius, Valeria; Knittel, Ria; Fallier-Becker, Petra; Amasheh, Salah (Frontiers in Physiology, 2020)
Claudin-5 determines the sealing properties of blood-brain barrier tight junctions and its function is impaired in neurodegenerative and neuroinflammatory disorders. Focusing on the contribution of claudin-5 to the trans-interaction within the tight junction seal, we used Xenopus laevis oocytes as an expression system. Cells were clustered and challenged in a novel approach for the analysis of claudin interaction. We evaluated the strengthening effect of claudin-5 to cell-cell-connection in comparison to claudin-3. Application of a hydrostatic pressure impulse on clustered control oocyte pairs revealed a reduction of contact areas. In contrast, combinations with both oocytes expressing claudins maintained an enhanced connection between the cells (cldn5–cldn5, cldn3–cldn3). Strength of interaction was increased by both claudin-3 and claudin-5. This novel approach allowed an analysis of single claudins contributing to tight junction integrity, characterizing homophilic and hetrophilic trans-interaction of claudins. To test a new screening approach for barrier effectors, exemplarily, this 2-cell model of oocytes was used to analyze the effect of the absorption enhancer sodium caprate on the oocyte pairs.